Just something. ;p1=1a=b-ab=-b(2)a(2)-ab=a(2)-b(2)a(a-b)=(a+b)(a-b)a=a+b1=2*(2) means to the power of two.

I don't quite understand how you're going from step to step. The equalities in lines 5 and 6 can't be true unless a and b are zero. The last statement should be 0=0.

I am not exactly sure what they are teaching you all in school anymore. Just because you know how to do basic Algebra - doesn't mean you can just pull variables out of nowhere and throw them into your equation

(a - b)(a + b) = b(a - b) I thinnk he tried to make it like this. But yes, there is a mistake in line 5.

What about this:1=1a=bLet's just substuitute a for b then:-a*a=-a(2)a(2)-a*a=a(2)-a(2)(We're doing good so far...)Falls apart here:a(a-a)=(a+a)(a-a)a=a+aa<>2a*(2) means to the power of two.

The problem as I see it is that (a-b)=0. Division by zero is undefined, since there is no number that, multiplied by zero gives you a number that is non-zero. So dividing both sides by (a-b) won't work.

I'm going to stick with undefined, buddy.Here's an interesting discussion which includes our (in)famous math problem:http://theobligatescientist.blogspot.com/2010/04/dividing-by-zero.html

lololololololololololololIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIiIlook! a bridge!

My calculus teacher told me that Stephen Hawking tried to divide by zero - and look at what happened to him